Prevalence of Intestinal Helminth Parasites of Chicken (Gallus gallus domesticus Linnaeus, 1758) in Lalitpur District, Nepal - Subedi, Janak Raj; Mujahid, Tasneem; Cheetri, Bijay (Tribhuvan University Journal, 2018)
This study was aimed to determine the prevalence of intestinal helminth parasites of local chicken (Gallus gallus domesticus) from Lalitpur district, Nepal. It was carried out from February 2014 to March 2015. A total of 125 samples (93 alimentary canals of freshly killed chicken and 32 stool samples from ground and fowl runs) were collected. Out of 93 alimentary canals 17 were collected from free range chicken and 76 were from slaughtered house i.e. from poultry farm chicken. The faecal samples were collected in the sterile vials containing 2.5 percent potassium dichromate. Depending upon the convenience, post mortem examination method, differential floatation method and direct smear method were used for the examination of samples. The present study showed only 40 percent of all the poultry examined as infected. Overall 5 species of nematodes, 1 species of cestode and 4 unidentified species were found to be prevalent in chicken from Lalitpur district. The highest prevalence rate was found with Heterakis gallinarum (22.4%) followed by Capillaria species (16%), Ascaridia galli (10.4%), unidentified species (4.8%) and Raillietina tetragona (4%). Statistically there was a significant difference in the prevalence of helminth species (χ2=33.83; p< 0.05; α=1). Likewise, there was significant difference in the prevalence rate of helminth parasites in free range chicken and poultry chicken (χ2=22.055; p< 0.05; α=1).